NEW APPROACHES TO TREATMENT METHODS FOR ACUTE OTITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The problem of acute inflammatory process of the middle ear has been relevant for ENT specialists for many years. It is known that foci of purulent infection can form in the cavities of the middle ear, which are the cause of persistent inflammatory process in the middle ear. The problem of acute otitis media is even more relevant due to its prevalence in early childhood: more than 65.0% of children under 3 years of age suffer from acute otitis media 1-2 times and 35.0% of children get sick 3 times or more functions. Acute otitis media in most cases with timely and adequate treatment ends with recovery and full restoration of hearing. However, with a decrease in the reactivity of the body, inadequate antibacterial therapy and untimely surgical treatment, acute inflammation of the middle ear can lead to persistent impairment of hearing function, chronicity of the process and even intracranial complications. Currently, various methods of treating exudative otitis media are used in clinical practice. They include conservative therapy methods and surgical treatment methods. Despite the variety of existing methods of treating exudative otitis media, they are not effective enough: relapses of the disease and the development of persistent conductive hearing loss are noted. Therefore, the development and use of new effective methods of treating exudative otitis media in children is an urgent problem of modern otolaryngology.